The great cholesterol myth : why lowering your cholesterol won't prevent heart disease-- ; and the statin-free plan that will - Bowden, Jonny; Sinatra, Stephen T. (Fair Winds Press, 2015)
Get proven, evidence-based strategies from the experts with The Great Cholesterol Myth Plus 100 Recipes. Heart disease is the #1 killer. However, traditional heart disease protocols--with their emphasis on lowering cholesterol--have it all wrong. Emerging science is showing that cholesterol levels are a poor predictor of heart disease and that standard prescriptions for lowering it, such as ineffective low-fat/high-carb diets and serious, side-effect-causing statin drugs, obscure the real causes of heart disease. Even doctors at leading institutions have been misled for years based on creative reporting of research results from pharmaceutical companies intent on supporting the $31-billion-a-year cholesterol-lowering drug industry. The Great Cholesterol Myth Plus 100 Recipes reveals the real culprits of heart disease, including: Inflammation, Fibrinogen, Triglycerides, Homocysteine, Belly fat, Triglyceride to HCL ratios, High glycemic levels, and offers 100 recipes that will help reduce the risk of heart disease. Bestselling health authors Jonny Bowden, Ph.D. and Stephen Sinatra, M.D. give readers a 4-part strategy based on the latest studies and clinical findings for effectively preventing, managing, and reversing heart disease, focusing on diet, exercise, supplements, and stress and anger management. Then enjoy delicious, heart-healthy meals from nutritionist Deirdre Rawlings, Ph.D., N.D. Get proven, evidence-based strategies from the experts with The Great Cholesterol Myth Plus 100 Recipes. MYTHS VS. FACTS Myth: High cholesterol is the cause of heart disease. Fact: Cholesterol is only a minor player in the cascade of inflammation which is a cause of heart disease. Myth: High cholesterol is a predictor of heart attack. Fact: There is no correlation between cholesterol and heart attack. Myth: Lowering cholesterol with statin drugs will prolong your life. Fact: There is no data to show that statins have a significant impact on longevity. Myth: Statin drugs are safe. Fact: Statin drugs can be extremely toxic including causing death. Myth: Statin drugs are useful in men, women and the elderly. Fact: Statin drugs do the best job in middle-aged men with coronary disease. Myth: Statin drugs are useful in middle-aged men with coronary artery disease because of its impact on cholesterol. Fact: Statin drugs reduce inflammation and improve blood viscosity (thinning blood). Statins are extremely helpful in men with low HDL and coronary artery disease. Myth: Saturated fat is dangerous. Fact: Saturated fats are not dangerous. The killer fats are the transfats from partially hydrogenated oils. Myth: The higher the cholesterol, the shorter the lifespan. Fact: Higher cholesterol protects you from gastrointestinal disease, pulmonary disease and hemorrhagic stroke. Myth: A high carbohydrate diet protects you from heart disease. Fact: Simple processed carbs and sugars predispose you to heart disease. Myth: Fat is bad for your health. Fact: Monounsaturated and saturated fats protect you from metabolic syndrome. Sugar is the foe in cardiovascular disease. Myth: There is good (HDL) cholesterol and bad (LDL) cholesterol. Fact: This is over-simplistic. You must fractionate LDL and HDL to assess the components. Myth: Cholesterol causes heart disease. Fact: Cholesterol is only a theory in heart disease and only the small component of LP(a) or "bb shot" LDL predisposes one to oxidation and inflammation.